Bendung Bertangga sebagai Alternatif pada Perencanaan Bangunan Irigasi - Denik Sri Krisnayanti; Very Dermawan; M. Solichin; Suhardjono Suhardjono; Dian Noorvy Khaerudin (Balai Teknik Irigasi, 2016)
Stepped weir is generally a modification on the downstream face of a standard ogee weir. The overflow on stepped weir classified in to three types: nappe flow, transition flow, and skimming flow. The skimming flow more used in planning the weir because almost all the operations of weir for large discharge. This study aimed to investigate and examine the advantages of stepped weir by conducting variations models such as slope angle of weir, number of steps, and the value of Froude number. In this research, the models test of stepped spillway carried out with two models of weir type were the ogee weir and the stepped weir. The slope of stepped spillway (θ) are used 30˚ and 45˚, the number of steps (N) are 40 and 20, and the critical depth to the height of steps (yc/h) ranging from 0,700 <yc/h<3.00 with the Froude number (Fr)< 10. The results showed that friction factor of Darcy-Weisbach (f) for the stepped weir is 0.311 which affect the value of energy loss. Levels of dissolved oxygen at stepped weir flow increased by 2.011% - 2.846%. The value of relative energy losses (ΔE1/E0) are 86.129% on the stepped weir and 72.466% on the ogee weir. The increase in value relative energy loss will affect the length of stilling basin in the downstream.